COMPETITIVENESS-BASED DEVELOPMENT STRATEGY FOR PURUN (TYPHA LATIFOLIA) CRAFTSMEN IN HAUR GADING SUB-DISTRICT, AMUNTAI, HULU SUNGAI UTARA DISTRICT DURING COVID-19 PANDEMIC PERIOD - Kadir; Yuliani R.; Hamdani; Yasin M. (Russian Journal of Agricultural and Socio-Economic Sciences, 2021)
Weaving purun (Typha latifolia) has been a hereditary culture for generations of women for approximately 500 years ago, including the people of Haur Gading District. Initially, purun (Typha latifolia) products were limited to household utensils, so that they developed into crafts and weaving activities became people's livelihoods. The research objective is to analyze the purun (Typha latifolia) product development strategy based on internal and external factors so that craftsmen can adjust to all conditions and business climate conditions, for example a decrease in economic activity as a result of activity restrictions during the Covid-19 pandemic period. This research uses qualitative research methods through Focus Group Discussion (FGD) and quantitative analysis using SWOT analysis. Based on primary data sources obtained through Focus Group Discussion (FGD) and questionnaires with 35 respondents through random sampling techniques in the assessment of SWOT analysis. Based on the results of the SWOT analysis, it is in Quadrant III, namely that the purun handicraft business has a large market opportunity. There are internal weaknesses in purun craftsmen which become an obstacle. The development strategy is WO (Weakness Opportunity), which is a strategy to improve internal weaknesses and strengthen opportunities to gain a bigger market share. This is supported by the results of the FGD stating that purun (Typha latifolia) craftsmen need (1) funding assistance in the production process (2) purun craftsmen need training to produce innovative products so that they can compete in the national market. The opportunity for purun (Typha latifolia) craftsmen is that the results of purun weaving are very attractive to the lower and upper middle levels. The results of this weaving are an effort to support the go - green movement. Weaving purun (Typha latifolia) is one of the local wisdoms so it needs to be preserved.